Tackling the changing landscape in medical schools post COVID-19 Pandemic / Rohana Abdul Ghani … [et al.] - Abdul Ghani, Rohana; Koshy, Marymol; Abdul Rahman, Thuhairah Hasrah (Universiti Teknologi MARA Cawangan Selangor, 2020)
Medicine has always been about evolving scientific knowledge, constantly changing across disciplines as well as over time. When clinicians were alerted on the emergence of the COVID-19 pandemic in late December 2019, everyone knew that the world was heading towards an avalanche of change, but no one could foresee how vast and deep the impacts were going to be. The recent months has shown us that public response to community control during a pandemic varies. The methods used to contain the pandemic deeply affected the day-to-day lives of the citizens. Although some understood the changes imposed on them, others opposed the regulations as unfair. Some obeyed, while others broke the rules that were meant to protect them. Whatever the reaction to the pandemic, millions of people around the world are now working from home and for most, it is for the first time.